Productive dynamics of Sugarcane (Saccharum officinarum l.) in the Brejo Paraibano Microregion, Brazil - Djair Alves da Mata; Daniel Alves da Mata; Valdeir de Souza Oliveira (Universidade Estadual de Alagoas, 2024)
The academic article analyzed the productive dynamics of sugarcane in the Brejo Paraibano Microregion from 2017 to 2022. The objective was to understand the factors influencing the performance of this agricultural culture, emphasizing the importance of efficient management of cultural practices and fertilization for the quality of sugarcane fields. The study methodologically involved data analysis and systematic review of specialized literature. The results indicated variations in planted area, quantity produced, and productivity, influenced by climatic conditions and agricultural practices. In summary, it was possible to conclude that sugarcane agricultural production is a complex and dynamic activity, with strategies and innovations linked to sustainability present in this context, aiming at the economic and social development of the Brejo Paraibano region. Sugarcane activity is a complex and dynamic activity in agricultural production, and it is possible to highlight the importance of an integrated and holistic approach to understanding and improving the sector's performance in the specific context of the Brejo Paraibano region. Keywords: Sugarcane Agriculture, Agricultural Management, Economic Sustainability.